2023
DOI: 10.1039/d3ya00075c
|View full text |Cite
|
Sign up to set email alerts
|

Defect chemistry and ion transport in low-dimensional-networked Li-rich anti-perovskites as solid electrolytes for solid-state batteries

Abstract: Solid-state batteries are attracting significant attention due to their plethora of potential advantages, including energy density gains and safety enhancements. The heart of this technology can be found in its...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 83 publications
3
7
0
Order By: Relevance
“…For example, in the recent study of Gu et al that used graph neural networks to predict the synthesizability of perovskites, eight antiperovskite systems, namely, Li 3 CHg, Li 3 BeIr, Li 3 CBe, Li 3 ClSr, Li 3 SPb, Li 3 FK, Li 3 BeTi, and Li 3 PMn, simultaneously displayed good synthesizability scores but low thermodynamic stabilities, especially when compared to those computed for Li 3 OBr and Li 3 OCl. A similar scenario was also observed in our recent work, where the zero-dimensional antiperovskite Li 6 OBr 4 displayed an exceptionally high Li-ion diffusion coefficient of 6.08 × 10 –9 cm 2 s –1 at 300 K but was unstable at higher temperatures and has yet to be experimentally realized. Such examples illustrate the importance of establishing a multitargeted search for novel solid electrolytes that focuses concomitantly on multiple properties (e.g., ionic conductivity, thermodynamic stability, electrochemical stability, and synthesizability) to avoid incomplete analyses that can lead to premature promising status declarations.…”
Section: Discovery Screening and Synthesizabilitysupporting
confidence: 87%
See 4 more Smart Citations
“…For example, in the recent study of Gu et al that used graph neural networks to predict the synthesizability of perovskites, eight antiperovskite systems, namely, Li 3 CHg, Li 3 BeIr, Li 3 CBe, Li 3 ClSr, Li 3 SPb, Li 3 FK, Li 3 BeTi, and Li 3 PMn, simultaneously displayed good synthesizability scores but low thermodynamic stabilities, especially when compared to those computed for Li 3 OBr and Li 3 OCl. A similar scenario was also observed in our recent work, where the zero-dimensional antiperovskite Li 6 OBr 4 displayed an exceptionally high Li-ion diffusion coefficient of 6.08 × 10 –9 cm 2 s –1 at 300 K but was unstable at higher temperatures and has yet to be experimentally realized. Such examples illustrate the importance of establishing a multitargeted search for novel solid electrolytes that focuses concomitantly on multiple properties (e.g., ionic conductivity, thermodynamic stability, electrochemical stability, and synthesizability) to avoid incomplete analyses that can lead to premature promising status declarations.…”
Section: Discovery Screening and Synthesizabilitysupporting
confidence: 87%
“…For example, we studied the doping of Li 3 OCl with F – and divalent cations (Mg 2+ , Ca 2+ , Sr 2+ , and Ba 2+ ) via defect and MD simulations and found that while F-doped Li 3 OCl displayed high dopant-vacancy binding energies and low conductivity, its Mg-doped equivalent showed high ionic conductivity and low migration barriers with low dopant-vacancy binding energies. F doping was also predicted to cause high dopant-vacancy binding energies in Li-rich low-dimensional-networked antiperovskites . As a result, a significant reduction in Li-ion diffusion and an increase in activation energy were observed in F-doped Li x OA x –2 (A = Cl, Br; x = 3–6).…”
Section: Doping Defects and Ion Transport Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations